2008
DOI: 10.1136/sti.2007.025700
|View full text |Cite
|
Sign up to set email alerts
|

Genotype distribution of Candida albicans strains associated with different conditions of vulvovaginal candidiasis, as revealed by microsatellite typing

Abstract: The frequency of C albicans strains with the dominant genotypes (A to D) from patients with severe VVC was significantly higher than that from patients with mild-to-moderate VVC, implying that the CAI genotype distribution of C albicans strains correlates with the severity of VVC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 32 publications
4
29
1
Order By: Relevance
“…Different genotyping methods may result in different groupings of isolates. For example, inconsistent with our observations based on CAI polymorphism (8,11), genotyping of vaginal C. albicans isolates by using randomly amplified polymorphic DNA (RAPD) analysis failed to show any relationship between genotypes and VVC patient groups (3,12). Another possible reason is that the genotype distribution patterns of VVC causing C. albicans isolates in Chinese and European women may be different.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Different genotyping methods may result in different groupings of isolates. For example, inconsistent with our observations based on CAI polymorphism (8,11), genotyping of vaginal C. albicans isolates by using randomly amplified polymorphic DNA (RAPD) analysis failed to show any relationship between genotypes and VVC patient groups (3,12). Another possible reason is that the genotype distribution patterns of VVC causing C. albicans isolates in Chinese and European women may be different.…”
Section: Discussioncontrasting
confidence: 52%
“…These two dominant genotypes were rarely found among isolates from extragenital sites (11). In addition, the distribution of the dominant genotypes correlated positively with the severity of VVC (8,11). These results suggested that C. albicans isolates with genotypes CAI 30-45 and CAI 32-46 might be more virulent and/or more resistant to the commonly used azole drugs than those with other genotypes as causative agents of vaginal infection.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…RAPD analysis has also been used to resolve populations in various species, such as S. cerevisiae, S. bayanus var. uvarum, C. albicans and C. glabrata [65][66][67][68][69][70][71][72]. One concern in using pattern-based identification techniques is reproducibility between laboratories, because small differences in PCR conditions may impact the species-specific patterns that serve as reference.…”
Section: Candida Dubliniensismentioning
confidence: 99%
“…Different primer pairs and also different combinations of primer pairs for the subtyping of C. albicans were reported elsewhere, see e.g. the works of Sampaio et al (2005) or Fan et al (2007).…”
Section: Introductionmentioning
confidence: 99%